Regional differences in the economical sustainability of sports halls - Kosztin, Nikolett; Balatoni , Ildikó (Applied Studies in Agribusiness and Commerce, 2016)
The precondition of a health conscious behaviour in a community is establishing a healthy development of the community, an important part of which is the community’s attitude to sports and health. A basic manifestation of this is whether the leadership of a specific settlement is committed to developing sports facilities and, on the other hand, to what extent residents make use of these facilities. The aim of our research was to point out the number of sports facilities currently available for catering everyday physical education introduced in 2012, leisure sports and competitive sport events in two different regions of Hungary. We also examined the resources available for maintaining the facilities and the degree to which existing facilities are exploited. Existing sports halls of the Northern Great Plain and Central Transdanubia were included in the research. We wish to emphasise, in regards to the infrastructural developments of the coming few years, that it is essential to consider the fact, even in the planning phase of facilities, that sport events in themselves do not make the facilities economically sustainable. JEL code: Z20